EBV and multiple sclerosis: expression of LMP2A in MS patients - Agostini, Simone; Mancuso, Roberta; Caputo, Domenico; Rovaris, Marco; Clerici, Mario (Frontiers in Neuroscience, 2024)
Several evidences, including increased serum titers of Epstein–Barr virus (EBV)-specific antibodies and the presence of EBV DNA in brain of patients suggest a possible role of this virus in the pathogenesis of Multiple Sclerosis (MS), a chronic neurodegenerative disease with an unknown etiopathology. Aim of the present study is to verify if the expression of LMP2A and EBNA-1, two EBV genes, is altered in MS patients. EBV viral load, LMP2A and EBNA-1 gene expression and EBNA-1 antibodies titers were evaluated in blood of EBV-seropositive MS patients (n = 57; 31 relapsing remitting –RRMS- and 26 progressive -PMS-patients) and age- and sex-matched healthy controls (HC, n = 49). Results showed that EBNA-1 and VCA antibodies titers are significantly augmented in MS patients compared to HC (p < 0.05 for both antibodies); detection of EBV DNA was more frequent as well in MS patients compared to HC, although without reaching statistical significance. Regarding viral gene expression, LMP2A was significantly more frequently detected and more expressed in MS patients compared to HC (p < 0.005) whereas no differences were observed for EBNA-1. Considering patients alone, EBNA-1 was significantly more frequent in PMS compared to RRMS (p < 0.05), whereas no differences were observed for LMP2A. Increased expression of the LMP2A latency-associated gene in MS patients supports the hypothesis that EBV plays a role in disease etiopathology.